Influence of the measurement medium and matrix modifiers on the determination of silicon in waters by graphite furnace atomic absorption spectrometry - M El Himri; A El Himri; A Pastor; M De La Guardia (Journal of Applied Sciences and Environmental Management)
An electrothermal atomic absorption (ETAAS) method has been developed for the direct determination of Si in natural waters. Measurements were carried out on previously alkalinized samples and using a mixture of Pd and Mg(NO3)2 as matrix modifier, with an ashing temperature of 1400 oC and an atomization temperature of 2400 oC. Transversally heated pyrolitically graphite tubes, equipped with Lfvov platform and Zeeman effect correction, was employed in this study. A limit of detection of 2.6 ƒÊg/L Si was obtained and accuracy was evaluated by analyzing two Standard Reference Material at different concentration levels, a good agreement (<5%) was obtained. This developed procedure was demonstrated of the need of using an alkaline medium for accurate Si determination by ETAAS.